Pelatihan Pembuatan Nugget Berbasis Pangan Lokal Kerang Darah sebagai Makanan Tambahan Balita Stunting: Training for Making Nuggets Based on Local Food of Blood Clams as a Supplementary Feeding to Stunting Toddlers - Radeny Ramdany; Ariani Pongoh (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Stunting is a condition of chronic malnutrition that causes poor posture and reduced cognitive abilities. The highest prevalence of stunting toddlers in West Papua Province was found in Sorong City, 52.58%. The purpose of the activity is to improve the understanding and skills of the community in making nuggets based on local food, blood clams as an alternative to zinc-rich supplementary food for handling stunting toddlers in Malawei Village, Sorong City. The methods used were counseling on stunting, assistance in introducing the nutritional content of blood clams and training on making nuggets made from blood clams, and local food innovation competitions. The results of the evaluation showed that there was an increase in participants' knowledge about stunting before and after being given education. In contrast, before the teaching was carried out, most participants had a low level of knowledge (46.7%). After being educated, most participants had a good level of knowledge (90.0%). Based on these results, it can be concluded that the expected target of this community service activity was achieved.